VD_FINDINFO HC / 2013 / 249 vom 3. April 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, LOYER, AUGMENTATIONEN GÉNÉRAL, FORMULE OFFICIELLE, NULLITÉ, ABUS DE DROIT, PRESCRIPTION, RÉPÉTITIONENRICHISSEMENT ILLÉGITIME | 2 CC, 4 CC, 253 CO, 269d CO, 305 CO, 67 al. 1 CO